Atributos Químicos do Solo sob Capim Mombaça Integrado com Aleias de Eucalipto. - Ricardo, Anderson da Silva (2023)
Knowledge of the spatial variability of soil chemical components are useful for the rational use of agricultural inputs, such as the localized application of soil acidity correctives and fertilizers. The objective of this work was the chemical analysis of an eutrophic Red Latosol under pasture cultivation of Megathyrsus maximum cv. Mombaça in an integrated system with Eucalyptus urophyla using multivariate analysis. The study was done in a farm located in the city of Palmeiras do Tocantins, with an area of 6.04 hectares under the integrated planting system of Megathyrsus maximum cv. Mombasa with double lines of Eucalyptus urophyla with an average spacing of 110 m between rows, in which 40 samples were collected at two depths, 0.00 - 0.10 m and 0.10 - 0.20 m. The soil was classified as a Red Eutrophic Latosol, the attributes of soil pH (CaCl2), Ca, Mg, Al, K, P, SB, CEC, H + Al and V were evaluated, as well as sand, silt and clay. With the results the data were submitted to descriptive analysis and subsequent of principal componentes analysis (PCA). In general the chemical soil atributes that most contribute to the formation of components, regardless of depth measurement: pH, Ca, Mg, P, H + Al, and only on the surface 0.00 - 0.10 m sand and clay . The variables that did not contribute to the formation of the components were Silt, Al, K, CEC and SB. Through the analysis of the main components it was possible to understand the dynamics of soil chemical attributes, to evaluate the chemical quality of the soil and to correlate with the management of liming and fertilization practiced in the farm.